The access of individuals to international justice - d (Oxford : Oxford University Press, 2011)
This title contends that the right of access to justice (at national and international levels) constitutes a basic cornerstone of the international protection of human rights, and conforms a true right to the law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Human rights; Justice, Administration of